New approaches towards explaining construction methods of the great pyramid at Keops Büyük piramitlerin inşasının Keops Piramidiyle açıklanması - Yılmaz, İsmail (Journal of Human Sciences, 2015)
The importance of the Keops pyramid in terms of size and mass, has led to the proposal of three theories as to its modes of construction. The first theory argues that elephants and soldiers were employed for this work, which suggests considerable application of muscle power. The second states that the quarried stone blocks were transported to the pyramid construction site using elephants on a weight-bearing mechanism. The third suggests that stone blocks carried to the pyramid, were first uplifted with brute force, following which they were carried to the top, using the principle of buoyancy of water, through a system of graded pools. Theories suggested for the construction of this pyramid, can be applied to that of other pyramids. This paper analyses the construction of pyramids in terms of issues related to the quarry, stages of transport of stones from the quarry to the pyramid site and the final construction stage. Based on the theories explained in this study, the time period for the construction of the pyramid will be calculated, using expected values derived from the four different pool systems. Özet Boyut ve kütle değerleriyle Keops Piramidi ön plana çıktığından, büyük piramitlerin inşası, bu piramit için geliştirilen üç teoriyle açıklanacaktır. Bu teorilerden birincisi, piramit inşasında kas gücünü zorlayan işlerde fil ve askerler çalıştırılabilir. İkincisi, ocaktan kesilen taş bloklar, ağırlık aktarmalı düzenekte filler kullanılarak, piramide taşınabilir. Sonuncusu, piramide taşınarak getirilen taş bloklar, kas gücünün üst sınırları zorlandığı noktaya kadar çıkarılıp, sonrasında basamaklı havuzlarda sıvının kaldırma kuvvetinden yararlanılarak üst noktaya kadar taşınıp piramit inşa edilmiş olabilir. Bu piramidin inşası için geliştirilen teoriler diğer piramitlerin inşası içinde kullanılabilir. Piramitlerin inşası; taş blokların alındığı ocak, taş blokları ocaktan piramide taşıma ve piramidin inşaat aşaması olarak üçe ayırıp, iki aşaması incelenecektir. Bu çalışmada ocak aşaması incelenmeyecektir. Burada verilecek teoriler için dört farklı havuz sistemine olası değerler verilerek piramidin inşaat süresi hesaplanacaktır.